2017
DOI: 10.1038/srep41861
|View full text |Cite
|
Sign up to set email alerts
|

Nickel biopathways in tropical nickel hyperaccumulating trees from Sabah (Malaysia)

Abstract: The extraordinary level of accumulation of nickel (Ni) in hyperaccumulator plants is a consequence of specific metal sequestering and transport mechanisms, and knowledge of these processes is critical for advancing an understanding of transition element metabolic regulation in these plants. The Ni biopathways were elucidated in three plant species, Phyllanthus balgooyi, Phyllanthus securinegioides (Phyllanthaceae) and Rinorea bengalensis (Violaceae), that occur in Sabah (Malaysia) on the Island of Borneo. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
69
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 62 publications
3
69
0
Order By: Relevance
“…In their native habitats, P. rufuschaneyi and R. cf. bengalensis occur on degraded ultramafic soils with extremely low available nutrients (van der Ent and Mulligan, 2015; Bouman et al, 2018;van der Ent et al, 2018). Hence, in situations when biomass production is not a priority (e.g., for phytoremediation purposes), these species can be employed without fertilizer application.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In their native habitats, P. rufuschaneyi and R. cf. bengalensis occur on degraded ultramafic soils with extremely low available nutrients (van der Ent and Mulligan, 2015; Bouman et al, 2018;van der Ent et al, 2018). Hence, in situations when biomass production is not a priority (e.g., for phytoremediation purposes), these species can be employed without fertilizer application.…”
Section: Discussionmentioning
confidence: 99%
“…Brearley (2005) found that P is one of the limiting nutrients for Dryobalanops lanceolata in a nutrient limitation experiment using a Malaysian ultramafic soil. We expected significant growth responses to P addition because of the limited mobility of P in soils (Nye and Tinker, 1977) and the extremely low P concentrations in highly weathered tropical ultramafic soils (Proctor, 2003;van der Ent et al, 2018). Elsewhere, pot experiments and field trials have shown positive responses of tropical forest tree seedlings to P (Burslem et al, 1995;Lawrence, 2001;Cai et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whittaker 1954;Main 1974;Main 1981;Galey et al 2017;Gonneau et al 2017;Van der Ent et al 2017;Van der Ent et al 2018). Although knowledge about relationships between metals with other elements or factors in plants is broad, it is still difficult to final identify the causes of differences in Ni, Cr, and Co content in plants from Polish ultramafic soils.…”
Section: Accumulation Of Metals By Plantsmentioning
confidence: 99%